The factors that influences social media marketing on consumers’ brand loyalty / Fatin Asfea Zaludin - Zaludin, Fatin Asfea (Faculty of Business and Management, 2019)
In this 21st century, technologies and internet have been widely used to communicate, searching information, socialize and do business globally. It is because latest technologies has improved with creative mechanism and be a part of people’s daily routines. Businesses are taking social media such as their platform to spread awareness and engage with customers to initiate a strong customer’s brand loyalty. Although social media is now currently used to market the brand, not every brand are effectively use this platform to gain brand loyalty from consumers. Besides, some of them are still using the conventional ways of marketing their product brand. In short, this study was aims to investigate the factors of social media marketing such as electronic word of mouth, online advertisement and brand image that are influencing consumers’ brand loyalty. Questionnaires as for the finding for this study will be distributed to targeted respondents using Google form and sent through social media. Respondents of the study will be selected using convenience sampling. After all the data were collected, Statistical Package for the Social Sciences (SPSS) will be used for data analysis. Overall, the results from data finding show there are all positive correlation between independent variables and dependent variable. These findings indicate that businesses that are using social media marketing platforms need to focus on enhancing the brand in social media to gain strong brand loyalty among consumers.